Double emulsion (water-in-oil-in-water) system in succinic acid extraction - A stability study - Jusoh, Norela (Italian Association of Chemical Engineering - AIDIC, 2018)
Emulsion liquid membrane (ELM) process is a very promising method for the industrial separation process. This system offers many advantages, including simple operation, high selectivity, low energy requirement, and simultaneous step of extraction and stripping process. One of the most important aspects for a successful ELM process is emulsion stability, which is governed by emulsion swelling and breakage. Research on the stability of ELM system have been widely reported, especially for primary emulsion (water-in-oil) but very limited in double emulsion (water-in-oil-in-water) stability aspect. In this study, the stability of water-in-oil-inwater (W/O/W) was investigated by varying surfactant concentration of sorbitan monooleate (Span 80) and polyoxyethylene sorbitan monooleate (Tween 80), agitation speed, and agitation time. The results showed that the most stable W/O/W emulsion was obtained at 5 % (w/v) Span 80, 1 % (w/v) Tween 80, 300 rpm agitation speed, and 3 min of agitation time with no emulsion breakage or swelling occurred. This stable emulsion system can promote high extraction efficiency, which is 70 % of succinic acid was extracted.